Connecting Analytical Thinking and Intuition And the Nights Abound with Inspiration - Omstedt, Anders (SpringerBriefs in Earth Sciences, 2016)
This book demonstrates how analytical thinking and intuition can be systematically connected and trained. It is illustrated by figures and photographs and includes creative and stimulating exercises. We are living in a world of increasing complexity, in which perceiving reality accurately is increasingly important and difficult. Society's need to address "global grand challenges" requires that the scientific community initiates inter-disciplinary research programmes. These are often far removed from current programmes, which are usually based on intra-disciplinary science. Improving our understanding of complex problems and communicating this understanding to a large group of people from different backgrounds represents an important educational challenge. Connecting Analytical Thinking and Intuition stimulates students and scientists to improve their skills in thinking, communicating and learning more about being humans. A guide to connecting analytical thinking and intuition is presented using the "dream group" method developed by Montague Ullman, in which a group of 6-8 people systematically and carefully helps the dreamer to appreciate dreams. The importance of good memory, which can be trained through recalling the dreams, is also discussed in relation to science and literature.